Multilateral bargaining with subjective claims under majority vs. unanimity rule: an experiment - Merkel, Anna; Vanberg, Christoph (Journal of economic psychology, 2023)
We experimentally investigate the effects of subjective claims in a multilateral bargaining game. Claims are induced by having subjects ‘produce’ the surplus to be divided by earning points in a quiz task. We use a Baron-Ferejohn framework. Our main treatment variable is the majority required to pass a proposal. Under unanimity rule, all proposals and agreements constitute convex combinations of the equal split and a division that is proportional to points earned in the productive task. Contrary to our predictions, this pattern largely persists under majority rule. In sharp contrast to prior experiments in which an exogenous surplus is divided using majority rule, few subjects attempt to build minimum winning coalitions in the presence of claims from production.
Online verfügbar 18. Januar 2023, Artikelversion 20. Januar 2023
Gesehen am 24.05.2023